Competencies of biology teachers in the Philippine secondary fishery schools - Nobleza, Tomasa L. 1930- (s.n.], 1966)
The author looked into the competencies of biology teachers in teaching biology in the secondary fishery schools. These include the professional competencies in the form of skills, knowledge and understanding needed by a biology teacher and the adequacy of the pre-service experiences of the teachers in developing these professional competencies.